Cytogenetic and molecular analysis of the Pantaneiro cattle breed - Issa, Érica Cunha; Jorge, Wilham; Sereno, José Robson Bezerra (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to characterize Pantaneiro cattle genetically through its paternal ancestry by the morphology of the Y chromosome, whether submetacentric or acrocentric, as well as to identify the maternal ancestry through mitochondrial DNA. The karyotype and mitochondrial DNA of 12 bulls of Pantaneiro breed were analyzed. The Y chromosome was analyzed in lymphocyte metaphases and the mitochondrial DNA by diagnosing its haplotype (Bos taurus and Bos indicus). Among Pantaneiro animals analyzed three had a taurine (submetacentric) Y and nine had a zebuine (acrocentric) Y chromosome, suggesting breed contamination by Zebu cattle, once Pantaneiro is considered to be of European origin. The mitochondrial DNA was exclusively of taurine origin, indicating that the participation of zebuines in the formation of the breed occurred entirely through the paternal line.